2020
DOI: 10.1002/ange.202000505
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2‐Oxazoline)‐Based Functional Peptide Mimics: Eradicating MRSA Infections and Persisters while Alleviating Antimicrobial Resistance

Abstract: Peptides have important biological functions. However, their susceptibility to proteolysis limits their applications. We demonstrated here for the first time, that poly(2‐oxazoline) (POX) can work as a functional mimic of peptides. POX‐based glycine pseudopeptides, a host defense peptide mimic, had potent activities against methicillin‐resistant S. aureus, which causes formidable infections. The POX mimic showed potent activity against persisters that are highly resistant to antibiotics. S. aureus did not deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 80 publications
1
22
0
Order By: Relevance
“…The increase in the ROS level might be due to greater cytosolic stress caused by the complementary functional mechanisms of polymer (binding with nucleic acids) and rifampicin (inhibition of nucleic acid synthesis). DNA binding by antimicrobial polymers was also observed by Zhou et al [47] to cause strong SOS response, leading to elevation of intracellular ROS level. [48] The rapid production of ROS implies a final effector role in bacterial cell death following treatment with polymer/rifampicin combination.…”
Section: Mechanistic Studymentioning
confidence: 64%
“…The increase in the ROS level might be due to greater cytosolic stress caused by the complementary functional mechanisms of polymer (binding with nucleic acids) and rifampicin (inhibition of nucleic acid synthesis). DNA binding by antimicrobial polymers was also observed by Zhou et al [47] to cause strong SOS response, leading to elevation of intracellular ROS level. [48] The rapid production of ROS implies a final effector role in bacterial cell death following treatment with polymer/rifampicin combination.…”
Section: Mechanistic Studymentioning
confidence: 64%
“…This suggested that an increase in the concentration of peptide resulted in an enhancement of ROS production, which indirectly affected the growth of S. aureus ATCC 25923. However, it is known that if the bacterial cells fail to minimize the excess of intracellular ROS production, membrane depolarization occurs, which ultimately leads to cell death ( Yadav et al, 2020 ; Zhou et al, 2020 ). The same phenomenon was observed in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Bithionol (10 μg/ml) was used as control. The fluorescence intensity was measured at the excitation wavelength of 622 nm with emission wavelength of 670 nm ( Zhou et al, 2020 ). The experiments were repeated in triplicate.…”
Section: Methodsmentioning
confidence: 99%